2017
DOI: 10.1007/s00520-017-3698-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-specific geriatric assessment and quality of life: important factors in caring for older patients with aggressive B-cell lymphoma

Abstract: A pre-treatment impaired functional status is an important factor with respect to clinical outcomes in patients receiving an R-BL regimen. Individual geriatric and related QoL domains showed similar associations with clinical outcomes. Whether interventions targeting specific geriatric dimensions also translate in better symptom- or domain-specific QoL warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
3
9
0
2
Order By: Relevance
“…Supporting this assumption, Ribi et al prospectively demonstrated CGA as an effective tool to identify frail patients with B-cell lymphoma. 38 Tucci et al reported CGA was efficient in identifying elderly patients with DLBCL who can benefit from the treatment with curative intent of immunochemotherapy. 18,19 Furthermore, modify immunochemotherapy tailored according to a CGA was associated with manageable toxicity and better outcome in elderly patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this assumption, Ribi et al prospectively demonstrated CGA as an effective tool to identify frail patients with B-cell lymphoma. 38 Tucci et al reported CGA was efficient in identifying elderly patients with DLBCL who can benefit from the treatment with curative intent of immunochemotherapy. 18,19 Furthermore, modify immunochemotherapy tailored according to a CGA was associated with manageable toxicity and better outcome in elderly patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, eight studies focused on a very specific treatment 20,23,24,31,51,55,56,60 which we considered as not fully representative of our target population. Overall, the duration of follow-up was sufficient but in nine studies the followup rate was less than 90% 24,30,46 or the adequacy of followup was not reported. 27,32,33,56,57,62 There were no other quality concerns.…”
Section: Quality Assessmentmentioning
confidence: 90%
“…The median sample size of the studies was 100 (range, 25-869), and the me(di)an age of included patients ranged from 58 to 86 years. Eight studies focused on acute myeloid leukemia and/or myelodysplastic syndromes, [19][20][21][22][23][24][25]27 two on chronic lymphocytic leukemia, 28,29 13 on lymphoma, [30][31][32][33][34][35][36][37][38][39][40][41][42] seven on multiple myeloma, [42][43][44][45][46][47][48] and 15 studies included various hematologic malignancies. [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The median number of domains addressed in the geriatric assessment was four (range, 2-9).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In these studies, these three tools were predictive of inferior outcomes after treatment of non-Hodgkin lymphoma with chemoimmunotherapy plus lenalidomide or R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone or prednisolone)-based chemotherapy. 35,40,41 Other frailty screenings-such as the Fatigue, Resistance, Ambulation, Illnesses, and Loss of Weight (known as FRAIL) scale or the Clinical Frailty Scale (CFS)-have been suggested for capturing frailty in older people. 42,43 Recently, in the wake of the COVID-19 pandemic, the CFS was propagated for use in the clinic to rapidly capture the frailty status of older people before the onset of their acute illness.…”
Section: Seriesmentioning
confidence: 99%